The Instrumental Rationality of Indigenous Leaders in Proposing Customary Forests within the Other Land Use Areas in Jangkat District, Merangin Regency, Jambi - Faruq El Pikaso; Afrizal Afrizal; Lucky Zamzami; Fikri El Gibran; Randrianiaina Jaona Eddie (LPPM Universitas PGRI Sumatera Barat, 2026)
Following Constitutional Court Decision No. 35/PUU-X/2012, the status of Customary Forests shifted from state forests to forests owned by indigenous people (Masyarakat Hukum Adat). This significant transformation in forest governance has triggered a surge in proposals to designate Customary Forests, which interestingly now extend to Other Land Use Areas (Areal Penggunaan Lain/APL), or non-forest plantation lands. Although legally permissible, the phenomenon of proposing Customary Forests on APL is unique in that indigenous people continue to propose them in areas they have owned since their inception. Therefore, this study analyzes why indigenous leaders propose the Customary Forest designation on APL in Jangkat District, Merangin Regency, Jambi. The theory used in this study is Weber’s instrumental rational action. This research employs a qualitative approach using data collection techniques such as literature study, in-depth interviews and FGDs with indigenous leaders and village officials. The results indicate that the primary rationality underlying the proposal is instrumental. Specifically, customary leaders are seeking formal recognition to access government support and assistance in protecting vital water sources that sustain community livelihoods and strengthen the certainty and security of customary communities' rights.